Equipo multidisciplinario en cirugía metabólica - Papapietro V., Karin (Revista Hospital Clínico Universidad de Chile, 2012)
Metabolic surgery may improve type 2 diabetes. However, diabetic patients have some pathophysiological characteristics that should be considered before facing a surgical treatment. Without an accurate selection and assessment of patients, surgical results may be limited and patients have risk of serious postoperative complications that may be nutritional and/or metabolic diseases. Clinical preoperative evaluations allow the analysis of the overall condition of the diabetic patients, preparing them for surgery and especially reducing perioperative risks. Psychological, nutritional and physical preparation can improve success expectations. Multidisciplinary monitoring reduces the risk of nutritional complications, promotes lifestyle change optimize the results and the long-term maintenance as it is known that weight re-gain can reverse the good metabolic results achieved. There is international consensus recommending to perform surgeries in centers of excellence with a coordinated team of trained professionals developing comprehensive treatment protocols with early and late follow up of patients and reporting the outcomes.